2020
DOI: 10.1097/md.0000000000017908
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between abdominal ultrasound and nuclear magnetic resonance imaging detection of placenta accreta in the second and third trimester of pregnancy

Abstract: This study is to determine accuracy of abdominal ultrasound and nuclear magnetic resonance imaging (MRI) for placenta accreta in the second and third trimester of pregnancy and to define the most relevant features of abdominal ultrasound and MRI for placenta accreta prediction. Between September 2012 and September 2018, 245 high risk of placenta accreta in the second trimester of pregnancy were prenatal diagnosed by abdominal ultrasound and MRI and they were followed up until the end of pregnancy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…Two studies reported the use of contrast medium 26,28 . Xia et al 28 conducted separate evaluations of two populations of women in different trimesters; six studies included participants in the third trimester [26][27][28][29]35,36 .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies reported the use of contrast medium 26,28 . Xia et al 28 conducted separate evaluations of two populations of women in different trimesters; six studies included participants in the third trimester [26][27][28][29]35,36 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Finally, it is unfortunate that we were unable to retrieve from most studies the following important patient selection details: (1) whether patients were included consecutively (i.e. whether all patients referred to the study center underwent ultrasound and MRI examinations or whether the assessments were offered only to selected subsets of women) and (2) risk factors for PAS, which were not disclosed clearly by four studies [26][27][28]32 .…”
Section: Pooled Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have also shown that missed diagnosis that occurs when MRI or ultrasound are used in isolation may be related to changes in bladder filling due to inflammation, the thickness of abdominal fat layer, and placenta position (22)(23)(24). Xia et al (25) found that combined ultrasound and MRI had higher sensitivity for placenta accreta diagnosis in the second trimester of pregnancy than ultrasound or MRI alone. This study also revealed that the combined ultrasound and MRI had significantly higher specificity and accuracy for the placenta accreta diagnosis either modality alone, reducing the risk of missed diagnosis and it implications.…”
Section: Discussionmentioning
confidence: 99%
“…11 While sonography is often the preferred single imaging modality for evaluating for PAS, the accuracy for diagnosing it remains higher when both sonography and MRI are conducted together (97.5%). 2,13…”
Section: Discussionmentioning
confidence: 99%